Feasibility of early fatigue damage evaluation using the Neutron diffraction method. (November 2022) - Vidler, James; Kotousov, Andrei; Hughes, James M.; Paradowska, Anna; Reid, Mark; Ng, Ching-Tai
Highlights: Field of residual micro-strains changes with accumulation of HCF damage. Hydrostatic residual micro-stress has a tendency to decrease with increasing HCF damage. Only severe fatigue damage can be evaluated with the Neutron Diffraction method. The full-width at half-maximum of the diffraction peak increases at high levels of damage. Abstract: One of the most successful applications of the Neutron Diffraction (ND) method is the evaluation of residual stress, specifically in welded structures, and many examples exists in the literature. The present study explores the feasibility of applying the ND method to the evaluation of early high-cycle fatigue damage (i.e. the damage prior to formation of fatigue micro- or macro-cracks). In metals and advanced alloys early fatigue damage is normally associated with the accumulation of irreversible and highly localised micro-plastic strains. These strains change the micro-strain/stress field on various scale levels. In this study we attempt to measure these changes applying the ND method to G350 steel fatigue samples, which have been relieved from residual stress and subjected to various degrees of high-cycle fatigue damage. Multiple measurements of the strain/stress field in each sample have been undertaken using the ND method with an incoming beam of 0.5×0.5 mm 2 . The outcomes demonstrate that it is feasible to evaluate severe fatigue damage using the ND method, and, in general, the severity of the fatigue damage correlates relatively well with the averaged hydrostatic component of the residual stresses measured by the ND. However, more accurate evaluation may require higher spatial resolution (smaller gauge length) and, possibly, a larger number of measurement points to improve the quality of the experimental data.